2019
DOI: 10.31234/osf.io/3wy47
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Thinking Twice About Sum Scores

Abstract: A common way to form scores from multiple-item scales is to sum responses of all items. Though sum scoring is often contrasted with factor analysis as a competing method, we review how factor analysis and sum scoring both fall under the larger umbrella of latent variable models, with sum scoring being a constrained version of a factor analysis. Despite similarities, reporting of psychometric properties for sum scored or factor analyzed scales are quite different. Further, if researchers use factor analysis to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…Not without controversy (see Supplement), factor scores are likely to be preferable to sum scores when ranking individuals on unobservable traits that are expected to be measured with noticeable measurement error (such as MPWB [32];). Similar approaches based on factor scoring have been successfully applied in large international assessment research [21,34].…”
Section: Development Of a Composite Measure Of Psychological Well-beimentioning
confidence: 99%
“…Not without controversy (see Supplement), factor scores are likely to be preferable to sum scores when ranking individuals on unobservable traits that are expected to be measured with noticeable measurement error (such as MPWB [32];). Similar approaches based on factor scoring have been successfully applied in large international assessment research [21,34].…”
Section: Development Of a Composite Measure Of Psychological Well-beimentioning
confidence: 99%
“…Sum or average scores serve as a rough approximation that are sometimes justifiable, but there are noted weaknesses with sum or average scores for reflective constructs, especially with longitudinal data (e.g., Braun & Mislevy, 2005;McNeish & Wolf, 2020). For instance, Kuhfeld and Soland (2020) noted that omitting the measurement model for outcome variables in longitudinal data has adverse effects on the parameter estimates.…”
Section: Measurement In Intensive Longitudinal Datamentioning
confidence: 99%
“…As can be seen in Figure 1, the factor analysis model of latent FC is a parameter-rich model that allows for differentially weighted relationships between the underlying latent connectivity and measured connectivity in each specific state. What McNeish and Wolf (2020) showed, however, is that the average can be recovered using this model by setting all factor loadings ( ) equal to 1 and the unique variances to 0. This recast of the average as a special case of the factor model not only has the advantage of making the assumptions of the average clearer, but it enables a formal test of those assumptions.…”
Section: Figure 1 Factor Modelmentioning
confidence: 99%
“…Given its ubiquity and close-formed, arithmetic solution, the average is rarely thought of as a formal statistical model. However, recent work (McNeish & Wolf, 2020) has shown that the average can be thought of as a restricted case of the more-general factor analytic model. Embedding the average in a theoretically rich statistical framework is likely to offer advantages for interpretation of results using this measure as well as insights into the measure itself.…”
Section: Introductionmentioning
confidence: 99%